2015
DOI: 10.1038/leu.2015.123
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of CD38 expression on multiple myeloma cells by all-trans retinoic acid improves the efficacy of daratumumab

Abstract: Daratumumab is an anti-CD38 monoclonal antibody with lytic activity against multiple myeloma (MM) cells, including ADCC (antibody-dependent cellular cytotoxicity) and CDC (complement-dependent cytotoxicity). Owing to a marked heterogeneity of response to daratumumab therapy in MM, we investigated determinants of the sensitivity of MM cells toward daratumumab-mediated ADCC and CDC. In bone marrow samples from 144 MM patients, we observed no difference in daratumumab-mediated lysis between newly diagnosed or rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
279
3
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 233 publications
(293 citation statements)
references
References 34 publications
7
279
3
4
Order By: Relevance
“…104 In Phase 2 studies the lower-dose of 10 mg/kg was associated with a longer PFS than the dose of 20 mg/kg (33 versus 19 months). 105 The results of the Phase 3 trial ELOQUENT-2 confirm the effect of elotuzumab in relapsed MM. 106 Daratumumab is an antibody that targets CD38 and kills plasma cells through ADCC and CDC mediated mechanisms.…”
Section: P Sonneveld Et Almentioning
confidence: 66%
“…104 In Phase 2 studies the lower-dose of 10 mg/kg was associated with a longer PFS than the dose of 20 mg/kg (33 versus 19 months). 105 The results of the Phase 3 trial ELOQUENT-2 confirm the effect of elotuzumab in relapsed MM. 106 Daratumumab is an antibody that targets CD38 and kills plasma cells through ADCC and CDC mediated mechanisms.…”
Section: P Sonneveld Et Almentioning
confidence: 66%
“…Indeed, certain agents are already being investigated for their ability to modulate CD38 expression for this purpose. For example, it was recently shown that all-trans-retinoic acid (ATRA) increased CD38 expression in multiple myeloma cell lines and in primary patient samples, significantly enhancing the effects of daratumumab in vitro and in vivo (42). Within the context of AML, ATRA is already being used as a therapy in the M3 subtype, acute promyelocytic leukemia, due to its ability to promote terminal differentiation of malignant cells.…”
Section: Discussionmentioning
confidence: 99%
“…We have recently demonstrated that the CD38 expression levels on MM cells are an important parameter for daratumumab sensitivity and proposed combining daratumumab with CD38 up-regulating agent all trans retionoic acid (ATRA). 4 Nonetheless, poor responses to daratumumab, observed even in the preshaematologica 2016; 101:e339 LETTERS TO THE EDITOR Figure 1. Bone marrow stromal cells (BMSC) protect multiple myeloma (MM) cells against daratumumab-induced antibody-dependent cellular cytotoxicity (ADCC) without CD38 modulation or immune suppression.…”
mentioning
confidence: 99%
“…Data are representative of 3 independent experiments. (B) In earlier developed assays, 4 BM-MNCs of 2 MM patients, from whom BMSCs were also available, were cultured in presence or absence of autologous BMSC for 16 h and then treated with daratumumab at indicated concentrations. Since bone marrow mononuclear cells (BM-MNC) already contain natural killer (NK) cells as effector cells, no additional effector cells were added.…”
mentioning
confidence: 99%
See 1 more Smart Citation